(untitled) (Research, Society and Development, 2020)
Rat as experimental model is a highly common practice in many areas of science. However, are not yet available studies using rats as a model for detecting changes in transformation of the muscle in meat. Thus, the objectives of this study were: (1) to describe and standardize the pH curve in transformation into meat of the muscles Triceps brachii, Longissimus dorsi and Biceps femoralis of rats subjected to normal breeding conditions from euthanasia to 24 hours post-mortem; and (2) to determine whether the stress by rats restraining in the ante-mortem period cause qualitative changes in meat and affects the time and pH values for the transformation of muscle in meat. For the determination of muscle pH curves were used 12 male Wistar rats. The animals were euthanized and the carcasses were placed under refrigeration for measurements of muscle pH. Another group of twelve animals was subjected to stress by restraining and after was performed the euthanasia and pH analysis. The results indicate that the values of pH post-mortem in the rat muscle showed similar decline according to commercial species. The muscle pH averages differ significantly from time 0 to 6 hours after slaughter (p<0.05), when the minimum value of muscle pH is found. Rats in restraint stress showed a decline in muscle pH significantly faster than normal curve (p<0.05). Rats are a promising experimental model to detect muscle post-mortem changes, because the decrease in the muscle pH follows the values and time similar to found in the commercial species.